Pengaruh Gaya Kepemimpinan Transformasional, Insentif Finansial Dan Komitmen Organisasional Terhadap Semangat Kerja Karyawan The Stones Legian Bali Hotel - Triyana, I Nyoman Yudi; Wibawa, I Made Artha (E-Jurnal Manajemen, 2014)
The purpose of this study was to determine the effect of transformational leadership style, financial incentives and organizational commitment to employee morale The Stones Legian Bali Hotel. This study used a quantitative research by using surveys and questionnaires to 96 respondents. Obtained findings that simultaneous variables of transformational leadership style, financial incentives and organizational commitment has a significant influence on employee morale The Stones Legian Bali Hotel. Other results found that in partial transformational leadership style, financial incentives and organizational commitment has a significant influence on employee morale The Stones Legian Bali Hotel. Finally, transformational leadership style variable is a variable that has the most dominant influence on employee morale The Stones Legian Bali Hotel.
Keywords: Style Transformational Leadership, Financial Incentives, Organizational Commitment, Employee Morale